2013
DOI: 10.1371/journal.pone.0068521
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cilia Are Lost in Preinvasive and Invasive Prostate Cancer

Abstract: Prostate cancer is the second most commonly diagnosed cancer in men worldwide. Little is known about the role of primary cilia in preinvasive and invasive prostate cancer. However, reduced cilia expression has been observed in human cancers including pancreatic cancer, renal cell carcinoma, breast cancer, cholangiocarcinoma, and melanoma. The aim of this study was to characterize primary cilia expression in preinvasive and invasive human prostate cancer, and to investigate the correlation between primary cilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 39 publications
1
97
0
1
Order By: Relevance
“…Conversely, primary cilia were neither increased nor decreased compared with normal tissue in lobular and ductal breast carcinomas or in gastric or prostatic adenocarcinoma. Interestingly, two recent studies report reduced numbers of primary cilia in prostatic cancer11 and breast cancer 12. The present study also found reduced frequency of primary cilia in these two cancer types (3.74% in prostatic cancer vs 8.07% in normal prostate and 1.8% and 4.44% in breast cancer vs 5.92% in normal breast tissue) but the results were not significant (p values 0.204 for prostatic and 0.061 and 0.169 for ductal cancer and lobular breast cancer, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, primary cilia were neither increased nor decreased compared with normal tissue in lobular and ductal breast carcinomas or in gastric or prostatic adenocarcinoma. Interestingly, two recent studies report reduced numbers of primary cilia in prostatic cancer11 and breast cancer 12. The present study also found reduced frequency of primary cilia in these two cancer types (3.74% in prostatic cancer vs 8.07% in normal prostate and 1.8% and 4.44% in breast cancer vs 5.92% in normal breast tissue) but the results were not significant (p values 0.204 for prostatic and 0.061 and 0.169 for ductal cancer and lobular breast cancer, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Primary cilia repress canonical Wnt signalling by constraining Jouberin (Jbn) to the ciliary axoneme and β-catenin to the basal body, limiting their entry into the nucleus and therefore downstream activation 11. The primary cilia also act as a signalling hub for the Hedgehog pathway, with both an oncogenic role and an inhibitory role depending on the cancer-initiating event18 and can facilitate the Hedgehog pathway by the expression of smoothened (smo) at the primary cilium, which is vital for Hedgehog signalling 4.…”
Section: Discussionmentioning
confidence: 99%
“…Other tumors presenting loss or decreased cilia expression include prostate, breast, melanoma, chondrosarcoma/enchondromas, and rhabdomyosarcoma, but the mechanisms involved in ciliary loss in these cancers remain to be elucidated [26, 3843]. …”
Section: Primary Cilia Fate In Cancermentioning
confidence: 99%
“…Here, we found a significant decrease in the ciliation rate of Sox10+ cells of acral melanoma (9%) vs acral nevi (74%) ( P ‐value <0.001), suggesting that loss of primary cilium may be either a causal or correlative factor during acral melanoma biogenesis. In addition, these data portray cilia loss as a common cellular feature of both acral melanoma and CMM as well as other types of malignancy . Nonetheless, the number of cases studied was small, and we believe our study should be interpreted as a pilot initiative, with findings that require validation by a larger study.…”
Section: Discussionmentioning
confidence: 85%